2012
DOI: 10.1111/j.1442-9071.2012.02813.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cediranib, an inhibitor of vascular endothelial growth factor receptor tyrosine kinase, in a mouse model of choroidal neovascularization

Abstract: Background: This study was conducted to evaluate the effect of cediranib, an inhibitor of vascular endothelial growth factor receptor tyrosine kinase, in a mouse model of laser-induced choroidal neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…Park et al investigated the effect of sorafenib, an orally administered, multi-targeted receptor tyrosine kinase inhibitor, on CNV progression in a rat CNV model, and showed that the drug inhibited laser-induced CNV [27]. Kang and co-workers evaluated the anti-angiogenic effects of the VEGF receptor tyrosine kinase inhibitor, cediranib, in an experimental laser-induced CNV model [28]. They found that oral administration of cediranib inhibited CNV growth.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al investigated the effect of sorafenib, an orally administered, multi-targeted receptor tyrosine kinase inhibitor, on CNV progression in a rat CNV model, and showed that the drug inhibited laser-induced CNV [27]. Kang and co-workers evaluated the anti-angiogenic effects of the VEGF receptor tyrosine kinase inhibitor, cediranib, in an experimental laser-induced CNV model [28]. They found that oral administration of cediranib inhibited CNV growth.…”
Section: Discussionmentioning
confidence: 99%
“…16 Briefly, after general anesthesia was induced via an intraperitoneal injection of 30 mg zolazepam (Zoletil; Virbac, Carros, France) and 10 mg xylazine hydrochloride (Rompun; Bayer, Leuverkeusen, Germany) per kilogram of body weight, laser-induced rupture of Bruch's membrane was performed on both eyes. Five laser spots were created per eye and delivered by slit lamp (SL120; Carl Zeiss Meditec, Jena, Germany).…”
Section: Animal Model Of Cnvmentioning
confidence: 99%
“…Fourteen days after laser injury, mice in each group were anesthetized and perfused through the left ventricle with 1.0 mL PBS containing 25 mg fluorescein isothiocyanatedextran (molecular weight, 2 3 10 6 kDa; Sigma-Aldrich Corp.), as described previously. 16,17 Eyes were enucleated and fixed in 4% paraformaldehyde for 1 hour. Retinal pigment epitheliumchoroid-sclera eyecups were prepared after hemisecting the eye, with total removal of the lens, vitreous body, and retina.…”
Section: Preparation Of Choroidal Flat Mountsmentioning
confidence: 99%
“…Thirty mice were randomly divided into three groups: vehicle‐treated mice ( n = 10), ALS‐L1023 (100 mg/kg/day)‐treated mice ( n = 10) and ALS‐L1023 (200 mg/kg/day)‐treated mice ( n = 10). Non‐treated mice (without vehicle) were not evaluated in the present study because our previous studies already demonstrated that vehicle (DMSO/0.5% carboxymethyl cellulose) does not cause any effect on CNV development . Vehicle and ALS‐L1023 treatment commenced at the onset of the experiments (day 0).…”
Section: Methodsmentioning
confidence: 99%